2015
DOI: 10.1175/jamc-d-14-0020.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Differential Reflectivity in Snowstorms and Warm Season Stratiform Systems

Abstract: The organized behavior of differential radar reflectivity (ZDR) is documented in the cold regions of a wide variety of stratiform precipitation types occurring in both winter and summer. The radar targets and attendant cloud microphysical conditions are interpreted within the context of measurements of ice crystal types in laboratory diffusion chambers in which humidity and temperature are both stringently controlled. The overriding operational interest here is in the identification of regions prone to icing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
3
22
1
Order By: Relevance
“…The results of the first combined polarimetric and Doppler spectral radar measurements in precipitating deep Arctic clouds presented herein are generally in agreement with previous studies performed in midlatitude stratiform clouds using longer-wavelength radars operating at S, C, and X bands (e.g., Andrić et al, 2013;Bechini et al, 2013;Griffin et al, 2017;Kennedy & Rutledge, 2011;Moisseev et al, 2015;Schrom et al, 2015;Schrom & Kumjian, 2016;Thompson et al, 2014;Williams et al, 2015). All of these studies document notable enhancement of Z DR and/or K DP in the DGL although the Z DR and K DP signatures may not occur simultaneously and not be collocated.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the first combined polarimetric and Doppler spectral radar measurements in precipitating deep Arctic clouds presented herein are generally in agreement with previous studies performed in midlatitude stratiform clouds using longer-wavelength radars operating at S, C, and X bands (e.g., Andrić et al, 2013;Bechini et al, 2013;Griffin et al, 2017;Kennedy & Rutledge, 2011;Moisseev et al, 2015;Schrom et al, 2015;Schrom & Kumjian, 2016;Thompson et al, 2014;Williams et al, 2015). All of these studies document notable enhancement of Z DR and/or K DP in the DGL although the Z DR and K DP signatures may not occur simultaneously and not be collocated.…”
Section: Discussionsupporting
confidence: 90%
“…For cases with D Ze > 2 mm, Z dr decreases with the increase of Z e . This relation is expected and has been reported before (e.g., Vivekanandan et al, 1994;Williams et al, 2015).…”
Section: From Radar Variables To Frsupporting
confidence: 89%
“…Sinclair et al (2016) have shown that such observations can be used to test representation of the secondary ice production in numerical weather prediction models. Other dual-polarization observations that show notable features are high-Z DR regions surrounding the cores of snow-generating cells (Kumjian et al, 2014) and at the top of ice clouds which can be linked to the presence of planar crystals and further to the presence of supercooled liquid water, providing very favorable conditions for their growth at these temperatures (Williams et al, 2015;Oue et al, 2016).…”
Section: Introductionmentioning
confidence: 99%